2010
DOI: 10.1590/s1677-55382010000100009
|View full text |Cite
|
Sign up to set email alerts
|

Duration of preoperative scrotal pain may predict the success of microsurgical varicocelectomy

Abstract: Purpose: Varicocelectomy is used in the treatment of scrotal pain. We report our results with microsurgical subinguinal varicocele ligation to treat pain. Materials and Methods: A total of 284 men underwent subinguinal microsurgical varicocele ligation for scrotal pain. All patients were asked to return for a follow-up evaluation 3 months after surgery, which included a physical examination, as well as questions on pain severity, number of days required before their return to work and development of any postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 21 publications
(10 reference statements)
6
34
0
Order By: Relevance
“…Varicocelectomy is one of the effective approaches for the treatment of varicocele and is associated with significant implication on sperm parameters, but after surgery, pain is the most important concern due to somatic and emotional effects on human life [1] [2]. There are several pharmacologic and non-pharmacologic methods to control of postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Varicocelectomy is one of the effective approaches for the treatment of varicocele and is associated with significant implication on sperm parameters, but after surgery, pain is the most important concern due to somatic and emotional effects on human life [1] [2]. There are several pharmacologic and non-pharmacologic methods to control of postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Concluded that using TENS acts as an index of important and efficient postoperative pain after inguinal hernia operation without side effects and continuation of pain reduction until one month [2]. Matthew et al demonstrated that TENS may reduce postoperative phantom pain on movement and at rest [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others did not find significant difference in varicocele grade between responders and non-responders. [7101116] In study by Chen et al . percentage of responders vs. non-responders in grade I, II, and III was 21.8% vs. 23.8%, 50.9% vs. 47.6%, and 27.3% vs. 28.6%, respectively.…”
Section: Predictors Of Successmentioning
confidence: 99%
“…Some studies have suggested that relief of pain after varicocele repair is independent of the type of pain (25), however, nearly all patients who had varicocele repair in this study had ''dull'' or ''throbbing'' pain prior to varicocelectomy. Other studies have related the relief of pain to the duration of pain; men with more chronic scrotal pain associated with varicocele are more likely to respond to surgical correction (25,26). Nearly every study recommends conservative measures (scrotal support, rest, etc) prior to consideration of varcicocelectomy.…”
Section: Testicular Painmentioning
confidence: 99%